2023
DOI: 10.1111/cns.14076
|View full text |Cite
|
Sign up to set email alerts
|

When the microbiome helps the brain‐current evidence

Abstract: The gut microbiota‐brain axis has been recognized as a network of connections that provides communication between the gut microflora and both central and autonomic nervous system. The gut microbiota alteration has been targeted for therapy in various neurodegenerative and psychiatric disbalances. Psychobiotics are probiotics that contribute beneficially to the brain function and the host mental health as a result of an interaction with the commensal gut bacteria, although their mechanism of action has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 153 publications
0
9
0
Order By: Relevance
“…These microorganisms can modulate individual behavior through various mechanisms, including metabolite, endocrine pathways ( Albillos et al, 2020 ). The gut microbiota’s involvement in the development of neurological disorders through the microbiota-gut-brain axis has been reported for some time ( Schorr and Miller, 2017 ; Mossad et al, 2021 ; Drljaca et al, 2023 ). However, the specific role played by individual microbial groups in this process remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These microorganisms can modulate individual behavior through various mechanisms, including metabolite, endocrine pathways ( Albillos et al, 2020 ). The gut microbiota’s involvement in the development of neurological disorders through the microbiota-gut-brain axis has been reported for some time ( Schorr and Miller, 2017 ; Mossad et al, 2021 ; Drljaca et al, 2023 ). However, the specific role played by individual microbial groups in this process remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a study conducted in 1932 confirmed the impact of L. acidophilus on individuals suffering from constipation and mental illness. 91 During the period spanning from the 1950s to the 1980s, the field of probiotic research mainly concentrated on examining various strains that might be obtained from natural sources or derived from human hosts, with a particular emphasis on identifying their methods of action. Further investigation has contributed to the development of knowledge regarding the intricate dynamics between the indigenous microbial communities and their capacity to withstand the infiltration of harmful bacteria, commonly known as colonisation resistance.…”
Section: Different Role Of Probiotics: a General Overviewmentioning
confidence: 99%
“…The latter study showed that fecal lipocalin-2 levels were associated with microbial beta diversity, which describes differential microbiome composition between two communities. Thus, fecal lipocalin-2 levels may emerge as a marker of microbiome dissimilarities ( Figure 2 ) [ 142 ], which are associated with neurological, tumor and liver diseases [ 32 , 144 , 145 ].…”
Section: Adipokines In Urine and Fecesmentioning
confidence: 99%
“…In regard to the utilization of feces for biomarker detection, it has emerged that the gut microbiome can greatly affect the composition of feces, potentially allowing bacterial metabolites to serve as biomarkers for different pathologies. In consideration that disturbed liver and bowel function, and various other disorders such as neurodegenerative diseases, are linked to changes in the microbiome and vice versa, analysis of fecal samples may be attractive for the identification of biomarkers for different diseases [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%